Assessment of Ionizing Radiation Effects on the Hematological Parameters of Radiation-Exposed Workers - H.N.E. Surniyantoro; T. Rahardjo; Y. Lusiyanti; N. Rahajeng; A.H. Sadewa; P. Hastuti; H. Date (PPIKSN-BATAN, 2019)
Long-term exposure to low doses of ionizing radiation may adversely affect human cells and tissues of hospital radiation workers, especially peripheral blood cell count. Blood cell count analysis is a useful screening test in a routine medical checkup. A high or low blood cells count even in a healthy-looking subject leads to the suspicion of disease and it should prompt further investigations. This study was aimed to assess the effects of ionizing radiation on the hematological parameters of radiation workers at several governmental hospitals in Indonesia and correlation between years of employment and equivalent dose on one hand and the hematological parameters on the other. It included 74 medical radiation workers occupationally exposed to low doses of ionizing radiation at the Unit of Radiology and Radiotherapy and 83 controls. Fourteen hematological parameters were measured by ABX Micros 60 Hematology analyzer and the correlation between years of employment and equivalent doseas well as hematological parameters on radiation-exposed workers were tested by linear regression analysis test. Our study reported that red blood cell and monocyte counts were significantly higher in radiation-exposed workers compared to controls, whereas white blood cells, hematocrit, mean corpuscular volume, and lymphocytes values were significantly lower in radiation-exposed workers. A significant correlation was observed between equivalent dose and red blood cells (RBCs) parameter (P=0.001) with a decline in RBC level of 0.541×106/µL per 1 mSv increase of radiation dose. The present study recommends that further studies shoulduse a larger sample size and include various independent variables (genetic polymorphism, chromosome aberration, micronucleus frequency) to study the long-term effects of low-dose radiation exposure on radiation-exposed workers.